2019
DOI: 10.1016/j.cageo.2019.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Bayeslands: A Bayesian inference approach for parameter uncertainty quantification in Badlands

Abstract: Bayesian inference provides a principled approach towards uncertainty quantification of free parameters in geophysical forward models. This provides advantages over optimization methods that provide single point estimates as solutions, which lack uncertainty quantification. Badlands (basin and landscape dynamics model) is geophysical forward model that simulates topography development at various space and time scales. Badlands consists of a number of geophysical parameters that need to be estimated with approp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 56 publications
1
40
0
Order By: Relevance
“…Figure shows an example of the posterior distributions for precipitation and erodibility, while fixing all other parameters for the CM problem. We note that our previous work (Chandra et al., ) showed that different combinations of precipitation and erodibility gave rise to visually indistinguishable topography for both the Cr and CM problem. Figure has a definite global maximum, but also several local maxima.…”
Section: Background and Related Workmentioning
confidence: 51%
See 4 more Smart Citations
“…Figure shows an example of the posterior distributions for precipitation and erodibility, while fixing all other parameters for the CM problem. We note that our previous work (Chandra et al., ) showed that different combinations of precipitation and erodibility gave rise to visually indistinguishable topography for both the Cr and CM problem. Figure has a definite global maximum, but also several local maxima.…”
Section: Background and Related Workmentioning
confidence: 51%
“…Note that the results for SC‐Bayeslands are taken from Chandra et al. () with 5% burn‐in, while PT‐Bayeslands features 25% burn‐in.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations